Śāsakīya karmacāriyoṃ ko daṇḍa : vibhāgīya jāñca se sambandhita mahatvapūrṇa ādeśoṃ kā saṅkalana, 14 Maī 1958 se 9 Apraila 1980 taka (Śāsana Kendrīya Mudraṇālaya, 1982)
Administrative regulations of the General Administration Dept. relating to departmental enquiry, punishment, etc.